Maternally Contributed Folate Receptor 1 Is Expressed in Ovarian Follicles and Contributes to Preimplantation Development - Strandgaard, Trine; Foder, Solveig; Heuck, Anders; Ernst, Erik; Nielsen, Morten S.; Lykke-Hartmann, Karin (Frontiers in Cell and Developmental Biology, 2017)
Folates have been shown to play a crucial role for proper development of the embryo as folate deficiency has been associated with reduced developmental capacity such as increased risk of fetal neural tube defects and spontanous abortion. Transcripts encoding the reduced folate carrier RFC1 (SLC19A1 protein) and the high-affinity folate receptor FOLR1 are expressed in oocytes and preimplantation embryos, respectively. In this study, we observed maternally contributed FOLR1 protein during mouse and human ovarian follicle development, and 2-cell mouse embryos. In mice, FOLR1 was highly enriched in oocytes from primary, secondary and tertiary follicles, and in the surrounding granulosa cells. Interestingly, during human follicle development, we noted a high and specific presence of FOLR1 in oocytes from primary and intermediate follicles, but not in the granulosa cells. The distribution of FOLR1 in follicles was noted as membrane-enriched but also seen in the cytoplasm in oocytes and granulosa cells. In 2-cell embryos, FOLR1-eGFP fusion protein was detected as cytoplasmic and membrane-associated dense structures, resembling the distribution pattern observed in ovarian follicle development. Knock-down of Folr1 mRNA function was accomplished by microinjection of short interference (si)RNA targeting Folr1, into mouse pronuclear zygotes. This revealed a reduced capacity of Folr1 siRNA-treated embryos to develop to blastocyst compared to the siRNA-scrambled control group, indicating that maternally contributed protein and zygotic transcripts sustain embryonic development combined. In summary, maternally contributed FOLR1 protein appears to maintain ovarian functions, and contribute to preimplantation development combined with embryonically synthesised FOLR1.